Warring societies of pre-colonial Southeast Asia local cultures of conflict within a regional context - Charney, Michael W.; Wellen, Kathryn Anderson (Copenhagen, Denmark NIAS Press, 2018)
"Why is it that warfare in Southeast Asian history is depicted so differently in various historical sources and representations? Why have scholars looking at different countries found so many exceptions to regional overviews of warfare? The present volume seeks to present a new approach to the study of warfare in the region by abandoning the generalizations made in the conventional literature. The contributors offer a range of new studies of warfare in local areas within the region, looking at warfare on its own, local terms rather than for what it says about warfare in the region as a whole. This approach for the first time submits Southeast Asia to comparative analysis in a way that avoids artificial and misleading regional attributes. The varied case studies, researched and written by a number of experts of local warfare within the region include naval warfare eighteenth century Vietnam, civil war in South Sulawesi during the Pâenâeki War, the art and texts of war in Burmese warfare, modes of warfare in precolonial Bali, war captive taking in Thailand, and kinship, religion, and war in late eighteenth century Maguindanao, and preparations for war in the Pacific rimlands. The volume makes an important contribution to the new literature emerging on the culture of indigenous warfare in North and South America, Africa, South Asia, the Middle East, and the Pacific Islands, by offering a new and robust Southeast Asian entry on the one hand while adding to a new approach to the growing literature on early modern Southeast Asia warfare."--Publisher's web sit
Warfare and depopulation of the Trans-Mekong Basin and the revival of Siam's economy / Puangthong R. Pawakapan -- La Maddukelleng and civil war in South Sulawesi / Kathryn Wellen -- Kinship, Islam, and raiding in Maguindanao, c. 1760-1780 / Ariel C. Lopez -- The age of the sea falcons: naval warfare in Vietnam, 1771-1802 / Vu Duc Liem -- Expansion and internalization of modes of warfare in pre-colonial Bali / Hans Hèagerdal -- Armed rural folk: elements of pre-colonial warfare in the artistic representations and written accounts of the Pacification Campaign (1886-1889) in Burma / Michael W. Charney -- Military capability and the state in Southeast Asia's Pacific Rimlands, 1500-1700 / Gerrit Knaap.
Includes bibliographical references (pages 201-221) and index.
In Englis
Keywords: Southeast Asia -- Politics and governmen; Southeast Asia -- History, Militar; Southeast Asia -- Histor; Southeast Asia -- Civilizatio